2009
DOI: 10.3109/08923970903213735
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of allergic diseases in an elderly population

Abstract: Recent years have shown a progressive increase of allergic disease in the elderly population worldwide. Naturally, this phenomenon has coincided with attempts to guarantee the best possible quality of life for this age group. As a result, diseases that were previously overlooked are attracting ever greater attention. An epidemiological study of allergic manifestations in the elderly conducted in all consecutive patients referred to an Allergology Unit over a three-month period at the beginning of 2008 showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
22
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 15 publications
2
22
0
3
Order By: Relevance
“…The frequency of rhinitis in the elderly has been addressed in very few elderly-targeted studies. Ventura et al (17) found that rhinitis was present in 16.8% of the patients aged over 65 years referred to an allergology unit. Population-based studies are even scarcer.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of rhinitis in the elderly has been addressed in very few elderly-targeted studies. Ventura et al (17) found that rhinitis was present in 16.8% of the patients aged over 65 years referred to an allergology unit. Population-based studies are even scarcer.…”
Section: Discussionmentioning
confidence: 99%
“…FA caused by fruits, vegetables, tree nuts, peanuts and seafood seem to be most prevalent in adults [9,10,21] . Sensitization may occur directly to food allergens or indirectly through cross-reactivity with aeroallergens.…”
mentioning
confidence: 99%
“…Figure 1 depicts the data of an Italian study from Bari conducted among 137 persons of at least 65 years of age (mean age 70.69 years; range 65-96) in 2008 [21] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Em relação à idade, existem poucos trabalhos abordando os quadros alérgicos em idosos [16][17][18][19][20][21][22][23][24][25][26][27][28][29], sendo que dois estudos nacionais apontaram uma alta prevalência de manifestações cutâneas nessa faixa etária, entre as quais a DC [21] e o prurido, como sintoma isolado [22].…”
Section: Discussionunclassified